Analisis Kemampuan Berpikir Kreatif Peserta Didik dalam Kegiatan P5 Tema Gaya Hidup Berkelanjutan - Alda Risma; Afrom, Ichyatul (PGSD FKIP UPR, 2025)
This study aims to describe the creative thinking abilities of fifth-grade students at SDN 10 Langkai during the implementation of the Pancasila Student Profile Strengthening Project (P5) on the theme of Sustainable Lifestyle. The study was motivated by a learning approach that gives students the freedom to create their own projects without predetermined models from the teacher. This research employed a descriptive qualitative method involving three students, using observation, interviews, and product assessments based on four creative thinking indicators: fluency, flexibility, originality, and elaboration. The findings indicate that students demonstrated creative thinking skills categorized as